2021
DOI: 10.1038/s41598-021-98819-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms involving diacylglycerol, ceramides, and inflammation underlie insulin resistance in oxidative and glycolytic muscles from high fat-fed rats

Abstract: This study investigated whether oxidative and glycolytic rat skeletal muscles respond differently to a high-fat (HF) sucrose-enriched diet with respect to diacylglycerol (DAG) and ceramides accumulation, protein kinase C (PKC) activation, glucose metabolism, and the expression of inflammatory genes. HF diet (8 weeks) suppressed insulin-stimulated glycogen synthesis and glucose oxidation in soleus (Sol), extensor digitorum longus (EDL) and epitrochlearis (Epit) muscles. However, DAG and ceramides levels increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
4
22
2
Order By: Relevance
“…2) The inhibition of AKT is mediated by accumulated ceramides. The novo synthesis of ceramides can be stimulated under different stress conditions; under overnutrition, saturated fatty acids (SFAs) can induce inflammation through the activation of toll-like receptor 4 (TLR4), which is related to the induction of the novo synthesis of ceramides (Holland et al, 2011;Ritter et al, 2015), and the increase of the proinflammatory interleukin synthesis, such as TNF-alfa or IL-6 (Jani et al, 2021).…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 99%
“…2) The inhibition of AKT is mediated by accumulated ceramides. The novo synthesis of ceramides can be stimulated under different stress conditions; under overnutrition, saturated fatty acids (SFAs) can induce inflammation through the activation of toll-like receptor 4 (TLR4), which is related to the induction of the novo synthesis of ceramides (Holland et al, 2011;Ritter et al, 2015), and the increase of the proinflammatory interleukin synthesis, such as TNF-alfa or IL-6 (Jani et al, 2021).…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 99%
“…Mitochondrial mass and oxidative capacity in skeletal muscle tends to be low in patients with these disorders, and studies suggest that people at increased genetic risk for diabetes tend to be deficient in this respect [ 277 , 278 ]. In the context of fatty diets and/or metabolic syndrome, impaired muscle capacity to oxidize fatty acids can lead to an accumulation of fatty acid derivatives in skeletal muscle—notably, diacylglycerol or ceramide—that, via activation of novel forms of protein kinase C and subsequent downstream activation of the kinases JNK and IKKβ, results in phosphorylations of insulin-responsive substrate-1 (IRS-1) that impede insulin signaling [ 279 , 280 , 281 , 282 ]. Concurrently, ceramide acts via atypical PKC-ξ and protein phosphatase 2A to suppress Akt activity [ 283 , 284 , 285 ].…”
Section: Some Agents Reducing Risk For Complications May Also Aid Ins...mentioning
confidence: 99%
“…Similarly, it has been proposed that ceramides promote the activation of atypical PKC isoforms (PKCζ/λ), which also impairs insulin‐stimulated AKT phosphorylation and its downstream signalling steps (Sokolowska & Blachnio‐Zabielska, 2019). Recent work from our lab (Jani et al., 2021) confirmed that male Wistar rats fed for 8 weeks an obesogenic high‐fat sucrose‐enriched (HFS) diet increased DAG and ceramide contents in Sol (highly oxidative muscle rich in type I fibres) (Ariano et al., 1973) and EDL (mixed muscle, rich in type I and IIa fibres) (Ariano et al., 1973), whereas in Epit muscles (highly glycolytic, rich in type IIa and IIb fibres) (Nesher et al., 1980) neither DAG nor ceramides were significantly elevated by the HFS diet. Moreover, whereas membrane‐bound PKCδ and PKCθ was increased in Sol and EDL, both PKC isoforms were reduced in Epit muscle from obese rats (Jani et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from our lab (Jani et al., 2021) confirmed that male Wistar rats fed for 8 weeks an obesogenic high‐fat sucrose‐enriched (HFS) diet increased DAG and ceramide contents in Sol (highly oxidative muscle rich in type I fibres) (Ariano et al., 1973) and EDL (mixed muscle, rich in type I and IIa fibres) (Ariano et al., 1973), whereas in Epit muscles (highly glycolytic, rich in type IIa and IIb fibres) (Nesher et al., 1980) neither DAG nor ceramides were significantly elevated by the HFS diet. Moreover, whereas membrane‐bound PKCδ and PKCθ was increased in Sol and EDL, both PKC isoforms were reduced in Epit muscle from obese rats (Jani et al., 2021). Hence, data from our previous studies provide evidence that glycerolipid and ceramide accumulation, as well as DAG‐induced PKC activation, follows a fibre type‐dependent pattern under conditions of diet‐induced obesity, and also that distinct mechanisms drive insulin resistance in oxidative and glycolytic muscles from male rats fed an obesogenic diet (Jani et al., 2021).…”
Section: Introductionmentioning
confidence: 99%